2010
DOI: 10.1080/00981389.2010.494561
|View full text |Cite
|
Sign up to set email alerts
|

Most Nursing Home Social Service Directors Lack Training in Working With Lesbian, Gay, and Bisexual Residents

Abstract: The purpose of this descriptive study is to report findings from a nationally representative mail-in survey of nursing home social service directors (n = 1,071) who were asked if they had received at least one hour of training in six different areas of cultural competency in the past five years. Of the six areas, the lowest percentage of directors reported having training in homophobia. Three-fourths of the sample had not received even one hour of homophobia training over the past five years. Directors who wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
45
0
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 63 publications
(57 citation statements)
references
References 12 publications
0
45
0
1
Order By: Relevance
“…Although many elder service agencies provide in-service trainings for staff, LGBT aging training is not commonly offered. A recently published national study surveyed over 1,000 nursing home directors and reported that 75% had less than 1 hr of training over the past 5 years on homophobia, heterosexism, and LGBT awareness (Bell, Bern-Klug, Kramer, & Saunders, 2010).…”
Section: Understanding a Lifetime Of Stigmamentioning
confidence: 99%
“…Although many elder service agencies provide in-service trainings for staff, LGBT aging training is not commonly offered. A recently published national study surveyed over 1,000 nursing home directors and reported that 75% had less than 1 hr of training over the past 5 years on homophobia, heterosexism, and LGBT awareness (Bell, Bern-Klug, Kramer, & Saunders, 2010).…”
Section: Understanding a Lifetime Of Stigmamentioning
confidence: 99%
“…Other results show that less than 25% of health service directors in nursing homes reported receiving training on homophobic health care practices within the previous five years (Bell, Bern-Klug, Kramer, & Saunders, 2010). These findings are concerning, as they represent a significant barrier to receiving competent care, and underscore the importance of addressing the attitudes and competencies of LTC health care providers and staff members.…”
Section: Homophobia and Heterosexism In Long-term Carementioning
confidence: 90%
“…Isolating the challenges LGBT individuals face in ACP imposed by social, legal, familial, and medical environments provides opportunities for service providers in these respective areas to prepare LGBT individuals in current and future aspects of end-of-life care. As this review indicated, researchers, practitioners, and service providers report a lack of knowledge of the health care disparities influencing the LGBT population, specifically, the potential for discrimination toward LGBT individuals served by health care delivery systems (Bell, Bern-Klug, Kramer, & Saunders, 2010;Hughes, Harold, & Boyer, 2011;IOM, 2011;Wheeler & Dodd, 2011). To minimize the potential for damage that occurs when heterosexual patients are favored over other types of patient populations (Neustifter, 2008), service providers must commit to educating themselves on the needs of the LGBT population (Browning, 2010).…”
Section: Implications For Practicementioning
confidence: 96%